2019
DOI: 10.3389/feart.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

Limitations Posed by Free DEMs in Watershed Studies: The Case of River Tanaro in Italy

Abstract: Topography is a critical element in the hydrological response of a drainage basin and its availability in the form of digital elevation models (DEMs) has advanced the modeling of hydrological and hydraulic processes. However, progress experienced in these fields may stall, as intrinsic characteristics of free DEMs may limit new findings, while at the same time new releases of free, high-accuracy, global digital terrain models are still uncertain. In this paper, the limiting nature of free DEMs is dissected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Limitations to this methodological approach are known. For instance, the GFI itself, as detailed by Manfreda et al (2014, 2015), Samela et al (2017), Tavares da Costa, Manfreda, et al (2019), and Tavares da Costa, Mazzoli, and Bagli (2019), is found to be less than optimal in identifying flood‐prone areas in flat terrain, which may explain the high FDR and overestimation. In other words, in a more incised fluvial valley, there are more independent GFI contours to choose from, which allows for a better representation of flood‐prone areas.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Limitations to this methodological approach are known. For instance, the GFI itself, as detailed by Manfreda et al (2014, 2015), Samela et al (2017), Tavares da Costa, Manfreda, et al (2019), and Tavares da Costa, Mazzoli, and Bagli (2019), is found to be less than optimal in identifying flood‐prone areas in flat terrain, which may explain the high FDR and overestimation. In other words, in a more incised fluvial valley, there are more independent GFI contours to choose from, which allows for a better representation of flood‐prone areas.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…However, such cases should be completely withheld from the performance analysis, as they might artificially influence the performance. Additional tests using the EU‐DEM, not reported here, have revealed that the use of a DEM to compute the GFI that is different from the DEM used in the modeling of the benchmark flood maps negatively influences the results. Caution should, thus, be exercised in the selection of the DEM, as in this study (a consistent use of the RMS‐DEM), but also in its processing (e.g., terrain analysis, river network, and catchment delineation; Tavares da Costa, Mazzoli, & Bagli, 2019). …”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottlenecks, such as the ones presented above, motivated a number of authors to produce alternative low-complexity solutions that rely on data-driven methods (Schumann et al, 2014a;Tang et al, 2018;Giovannettone et al, 2018;Caprario & Finotti, 2019;Zhao et al, 2019). Some take advantage of the causality between historical floods and the floodplain hydraulic geometry (e.g., Bhowmik, 1984;McGlynn and Seibert, 2003;Dodov and Foufola-Georgiou, 2006) and make use of digital elevation models (DEMs) that are datasets representing the Earth's surface, distributed as gridded values of local terrain elevations (Tavares da Costa et al, 2019b). For example, Nardi et al (2006Nardi et al ( , 2013Nardi et al ( , 2019, Morrison et al (2018) and Annis et al (2019) employed a flat-water approach (i.e., intersection of a water level with the surrounding DEM, or a variation of it, such as the HAND -Height Above the Nearest Drainage; Rennó et al, 2008;Nobre et al, 2016) to delineate floodplains.…”
Section: Introductionmentioning
confidence: 99%